Short‐term impacts of the 2019–20 fire season on biodiversity in eastern Australia. (17th October 2022) - Price, Owen F.; Mikac, Katarina; Wilson, Nicholas; Roberts, Bridget; Critescu, Romane H.; Gallagher, Rachael; Mallee, Justin; Donatiou, Paul; Webb, Jonathon; Keith, David A.; Letnic, Michael; Mackenzie, Berin D.E.
Abstract: To address uncertainties surrounding the impacts of unprecedented 2019–20 bushfires in south‐eastern Australia, we convened a symposium on field‐measured impacts on biodiversity for the 2020 Ecological Society of Australia conference. Nine presentations covered a range of studies on plant species and communities, and reptiles and mammals. Here, we summarize the presentations and review other field studies from NSW, some of which are currently unpublished. The impacts were extensive, but results also estimated survival rate perhaps higher than first reported in the media. More than half of individual mammal, reptile and threatened rainforest trees may have survived the fire, though small populations remain very vulnerable to second fire in the near future. Comprehensive understanding of the impacts of these fires requires much more field study, and for the results to be interpreted in the context of the broader fire regime. The symposium was an important early step in that understanding. Abstract : We conducted a symposium at the 2020 Ecological Society of Australia conference on the impacts of the 2019–20 bushfires, focusing on field survey of plants and animals. We found more than half of individual mammal, reptile and threatened rainforest trees may have survived the fire, though small populations remain very vulnerable to second fire in the near future.